Performance of reinforced concrete wall foundation connection under lateral cyclic load / Nurul ‘Aadila Saleh - Saleh, Nurul ‘Aadila (Faculty of Civil Engineering, 2012)
High-rise buildings are typically designed wall and foundation to resist the load during windstorms and earthquakes. Although performance of reinforced concrete wall foundation connection under lateral cyclic load are generally understood for construction, the research is needed to characterize the behavior and strength of the connection between wall-foundation to develop recommendation for designing wall foundation to resist load from seismic or wind events. The nature problem of concrete such as cracking and brittleness has become major problem especially when it comes to the weaker point of a stucture which is the connection. This study is conducted to determine the structural behaviour and crack pattern of RC wall-foundation connection under cyclic loads. Based from the load displacement profile, the load-displacement profile behave linearly before reached the yield point. A crack can be seen at the line of the connection between wall and foundation. Then, the load applied was increased until the sample reached the maximum strength and after that the load started decreasing and the cracks become bigger and wider. In terms of structural behavior of the wall, the reinforcement at the center was able to develop larger strain value compared with top and bottom reinforcement. Thus, it show the structural failure most occurred at the connection that influence the strength of the connection itself.